An Overview of Applications of Medical Barley Water in Gastrointestinal Disorders from the Viewpoint of Avicenna - Farzaneh Zare; Mohammad Mahd Parvizi; Mehrdad Karimi; Amir Mohammad Jaladat (Tehran University of Medical Sciences, 2024)
Gastrointestinal disorders are one of the most common conditions among people in many societies. On the other hand, evidence shows that the prevalence of usage of complementary and alternative medicine (CAM) has increased in recent years to treat many chronic and acute conditions, which might be due to testimonies of the safety, effectiveness, and affordability of CAM. In Persian medicine (PM), medical barley water (MBW) has been known as a helpful remedy for treating some digestive illnesses. This study aimed to review the properties of MBW in Avicenna's Canon of Medicine for the treatment of gastrointestinal disorders. So, Avicenna's Canon of Medicine was reviewed with keywords related to this remedy. Furthermore, various databases, including PubMed, Scopus, Web of Science, Google Scholar, and SID, were searched with the keywords "barley water," "non-alcoholic beer," and "alcohol-free beer." This study showed that Avicenna's Canon of Medicine recommends MBW for the treatment of various gastrointestinal disorders. Avicenna prescribed barley water for the treatment of bowel obstruction disease, bowel mass, intestinal ulcers, and jaundice. Oral consumption of MBW was the most frequently used method for disease improvement. Meanwhile, recent studies have also shown the therapeutic effects of non-alcoholic beer in the treatment of various disorders, such as gastrointestinal inflammatory disease, cardiovascular disease, and diabetes, possibly due to its anti-inflammatory effect. Given the high importance of MBW in Avicenna's Canon of Medicine, the results of this review and recent clinical studies can introduce MBW as an effective and less harmful gastrointestinal drug. We suggest conducting further clinical trials to assess the effectiveness of MBW in managing gastrointestinal conditions.